DAMPAK KINERJA KEPALA MADRASAH DALAM MENINGKATKAN PRESTASI SISWA MADRASAH TSANAWIYAH DESA NGELESAN KECAMATAN WIDODAREN KABUPATEN NGAWI - Luluk Muasomah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2021)
Abstract Good cooperation in educational institutions at Madrasah Tsanawiyah is predicted to improve student achievement. This is because the head of the madrasa as a leader, manager, administrator, and supervisor cannot automatically produce outstanding students without the help of Islamic religious education teachers. The research consists of the formulation of the problem: (1) How is the performance of the madrasa principal in managing student education at Madrasah Tsanawiyah? (2) How is the performance of the principal in improving student achievement at Madrasah Tsanawiyah? (3) The impact of the principal's performance in improving student achievement at Madrasah Tsanawiyah?. This research is a qualitative research with purposive sampling technique. The peculiarity of this purposive sampling technique is that samples can come from anywhere according to the objectives of the researcher. The results of this study, it is known that the performance of the head of Madrasah Tsanawiyah has an impact on increasing student achievement, namely exact and non exact. Exact achievement is an achievement related to the results of the evaluation of subjects such as; the value of student learning outcomes in UAM for the last 5 years. Meanwhile, non-academic achievements can be in the form of competitions participated by Madrasah Tsanawiyah students such as; Tilawatil Qur'an, Sports and Scouts. The increase in achievement has led the head of Madrasah Tsanawiyah to carry out formal and non-formal efforts. Namely with BBI (Intensive Tutoring. Based on these efforts, the achievement of Madrasah Tsanawiyah students is currently quite satisfactory, both academic and non-academic. Keywords: Principal, Policy, MTs Ngelesan